Iterative Methods for Solving the Proximal Split Feasibility Problems - Mamat, Manatsawin; Suparatulatorn, Raweerote; Cholamjiak, Prasit (Communications in Mathematics and Applications, 2019)
In this work, we study the proximal split feasibility problem. We introduce a new algorithm with inertial technique for solving this problem in Hilbert spaces. We also prove the strong convergence theorem under some suitable conditions. Finally, we give some numerical experiments to support our results.